Prevalence of Frailty and Prefrailty in People With Human Immunodeficiency Virus Aged 50 or Older: A Systematic Review and Meta-Analysis. (10th April 2022) - Yamada, Yuji; Kobayashi, Takaaki; Condo, Angela; Sangarlangkarn, Aroonsiri; Ko, Fred; Taniguchi, Yu; Kojima, Gotaro
Abstract: Background: With effective antiretroviral therapy, there is an emerging population of adults aged 50 years or older with human immunodeficiency virus (HIV). Frailty is an increasingly recognized clinical state of vulnerability associated with disability, hospitalization, and mortality. However, there is a paucity of large studies assessing its prevalence in people with HIV (PWH) aged 50 or older. Methods: PubMed was systematically searched for studies published between January 2000 and August 2020 reporting the prevalence of frailty in PWH aged 50 or older. The pooled prevalence of frailty and prefrailty was synthesized using a random-effects meta-analysis. Results: Of the 425 studies identified, 26 studies were included in the analysis, with a total of 6584 PWH aged 50 or older. The included studies were published between 2012 and 2020, and all studies used the Fried frailty phenotype to define frailty. The overall pooled prevalence of frailty and prefrailty was 10.9% (95% confidence interval [CI], 8.1%–14.2%) and 47.2% (95% CI, 40.1%–54.4%), respectively. A high degree of heterogeneity was observed (I 2 = 93.2%). In the subgroup analysis, HIV-related variables and other demographic variables were examined, and heterogeneity disappeared only in the group of a longer duration since HIV diagnosis (I 2 = 0%). Conclusions: The pooled prevalence of frailty and prefrailty defined by the Fried frailty phenotype was assessed in PWH aged 50 or older. Findings from this study quantified the proportion of this specific population with this common geriatric syndrome. Future studies identifying effective strategies for frailty screening and intervention are required for this vulnerable population. Abstract : The studies identified by our systematic review demonstrated a wide range of frailty prevalence among people with HIV aged 50 or older. The meta-analysis showed the pooled prevalence of frailty and prefrailty in this population was 10.9% and 47.2%, respectively.